Integrating requirements for the delivery of information relating to construction–product compositions. Issue 5 (August 2014) - Azuma, Kenichi; Funaki, Rika; Hasegawa, Ayumi; Shinohara, Naohide; Yamaguchi, Makoto; Fujita, Kiyo-Omi; Kikuchi, Yusuke; Tanabe, Shin-Ichi
Information on the compositions of construction products is useful to construction designers, builders and occupants to help establish good indoor air quality and building environment. Existing measures to deliver this information, such as labelling or material safety data sheets, have not been adequate for construction products. The study aims to evaluate the status of the current information-delivery system and clarify requirements for a future system. A questionnaire survey on the current status and requirements of an information-delivery system for construction-product compositions was conducted in Japan. In total, 203 manufacturers, including two associations, and 35 users responded. Responses relating to 439 and 226 products from manufacturers and users, respectively, were obtained. Majority of the manufacturers and users responded that a standardized scheme is needed. Large discrepancies were noted between the delivery levels required by users and the actual levels from manufacturers in terms of the information-delivery range and display elements. The limitations of information delivery for manufacturers differed between composite products or equipment and products in which the compositions played an important role in quality and performance. Concerns included the cost and manpower required to examine the compositions for new information-delivery system and the importance of maintaining consistency with existing systems.